Structure of locally graded CDN[)-groups - Semko, N. N. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We introduce the notion of CDN[)-groups:G is a CDN[)-group if, for any pair of its subgroupsA andB such thatA is a proper nonmaximum subgroup, ofB, there exists a normal subgroupN which belongs toG and satisfies the inequalitiesA≤N